2022
DOI: 10.3389/fimmu.2022.1037128
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of immunogenic cell death-related signature for predicting the prognosis and immune landscape of uveal melanoma

Abstract: IntroductionUveal melanoma (UM) is the most common primary intraocular malignant tumor in adults, and the main treatment for UM is currently surgery and plaque brachytherapy. UM is highly susceptible to metastasis, which eventually occurs in nearly half of all patients; once metastasis occurs, patients have a poor prognosis and the condition is difficult to treat. Therefore, the identification of new and effective UM biomarkers is vital for the application of therapeutic strategies. Immunogenic cell death (ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“… 62 , 63 Because of the pivotal and intriguing roles of various PCDs in cancer, abundant multi-gene signatures based on individual PCD forms have been developed and shown great promise in predicting clinical outcomes, drug resistance, and response to ICIs in cancer, such as pyroptosis, ferroptosis, autophagy, ICD, and the recently emerged cuproptosis. 18 , 19 , 20 , 21 , 23 , 64 , 65 However, the different PCDs are not absolutely mutually exclusive. Many redundancies and crosstalks have been observed among the signalling pathways regulating these cell death modalities, suggesting they may collectively affect tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 62 , 63 Because of the pivotal and intriguing roles of various PCDs in cancer, abundant multi-gene signatures based on individual PCD forms have been developed and shown great promise in predicting clinical outcomes, drug resistance, and response to ICIs in cancer, such as pyroptosis, ferroptosis, autophagy, ICD, and the recently emerged cuproptosis. 18 , 19 , 20 , 21 , 23 , 64 , 65 However, the different PCDs are not absolutely mutually exclusive. Many redundancies and crosstalks have been observed among the signalling pathways regulating these cell death modalities, suggesting they may collectively affect tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 16 Over the past years, tremendous efforts have been made to develop predictive models with signature genes of single PCD forms, and moderate predictive accuracy is achieved in predicting cancer prognosis and drug resistance. 17 , 18 , 19 , 20 , 21 , 22 , 23 However, considerable redundancy and crosstalk have been observed among the signalling pathways regulating diverse cell death forms. Therefore, it is reasonable to speculate that a predictive model based on all known PCD types should better represent tumour characteristics than single types of cell death.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the TCGA training cohort and two GEO validation cohort, patients with high-score of immunogenic cell death had worse prognosis than patients with low-score in ovarian cancer [54]. In uveal melanoma, a 5-gene ICD related genes risk signature was constructed, signature with high score had more immune cell in ltration and a worse prognosis than the low score group [55]. ICD related genes signature was evaluated in many types of cancers, but in LUAD, the research is still not clear.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The mediation of PCD is closely associated with the prognostic assessment of cancer patients, and the mining of prognostic signature markers based on PCD-related genes has been assigned significant value. 9 For example, Sha et al 10 revealed that two gene clusters associated with copper death in breast cancer present a potential impact on patient prognosis by regulating the level of immune cell infiltration in the tumor immune microenvironment. A study similar to the present one developed a prognostic risk model for hepatocellular carcinoma based on three key genes for PCD (GCSH, LIPT1 and CDKN2A) by means of biosignatures and validated the promotional effect of LIPT1 on hepatocellular carcinoma cell proliferation, invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Programmed cell death (PCD) includes apoptosis, necroptosis, autophagy, ferroptosis, pyroptosis, necrosis and copper death, and inducing the programmed death of cancer cells may help to assist in solving the problem of cellular drug resistance generation, which is beneficial to the mining of novel targets and targeted therapeutic drug development 7,8 . The mediation of PCD is closely associated with the prognostic assessment of cancer patients, and the mining of prognostic signature markers based on PCD‐related genes has been assigned significant value 9 . For example, Sha et al 10 revealed that two gene clusters associated with copper death in breast cancer present a potential impact on patient prognosis by regulating the level of immune cell infiltration in the tumor immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%